High performance supercapacitive behaviors of oximes in a poly(aniline-co-pyrrole) based conducting polymer structure - Basili, Taskin; Yildirim Kalyon, Hilal; Gencten, Metin; Macit, Mustafa; Sahin, Yucel (ROYAL SOC CHEMISTRY, 2023)
Novel oxime compounds and their complexes were synthesized and used as additives to poly(aniline-co-pyrrole) for the first time in the literature. The oxime compound (HL) and its complexes (M(HL)(2), M: Cu, Ni or Co) were characterized using spectroscopic methods such as FT-IR and NMR. Further, these materials were used as additives in the electrochemical preparation of the copolymer. Prepared electrodes consisting of the copolymer and M(HL)(2) (M: Cu, Ni or Co) were also characterized by FT-IR spectroscopy and scanning electron microscopy analyses. Electrochemical characterization of the modified electrodes was performed using the cyclic voltammetric method and electrochemical impedance spectroscopy. Capacitive behaviors of the modified electrodes were determined by cyclic charge-discharge tests. The areal capacitance of PGE/(PAn-co-PPy)@[Cu(HL)(2)] was 765 mF cm(-2), PGE/(PAn-co-PPy)@[Ni(HL)(2)] 816 mF cm(-2) and PGE/(PAn-co-PPy)@[Co(HL)(2)] 1024 mF cm(-2), with 10 mA cm(-2) charge/discharge current densities. This result showed that oxime compounds have great potential to obtain high performance supercapacitors.
Keywords: VIC-DIOXIME LIGAND; ENERGY-STORAGE; POSITIVE ELECTROLYTE; REDOX PROPERTIES; COMPLEXES; POLYANILINE; POLYPYRROLE; COMPOSITES; NI(II); MONONUCLEAR; Chemistry